Autonomías indígenas en la Amazonía peruana. La experiencia del pueblo wampis - Pérez, Wrays (2019)
This article presents an account of the memory an historic experience of the Wampis people through different political regimes that have tried to influence and intervene in the governance of the ancestral territory. It wants to offer a vision of their interaction with these regimes, taking as a startpoint their collective memory. The article collects some of the central characteristics of the Wampis’ experience in handling and defending their territory facing the institutional changes that are lived in the high Amazon. So, the article takes into account the problems related to the intensification of the influence of the national Peruvian state and the trade pressure that tries to make deep changes in the territory, due to the extension of legal and illegal border economies, as well as demographic changes. Then, the article shows the response of Wampis, which conforms their proposal of an autonomous territorial government.